HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN PASSING PADA PERMAINAN SEPAK TAKRAW SISWA SMPN 1 TELUK KUANTAN - Dian Anggraini; Drs. Saripin., M.Kes AIFO '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this study were students in movement, especially at the time of passing students have not been so good, it is suspected because of foot-eye coordination is not optimal. This study aims to determine whether there is a corelation between eye coordination and foot with passing ability in the game of sepak takraw at students of SMP Negeri 1 Teluk Kuantan, in this study a sample of the entire population of students who take extra sepak takraw with a total of 36 people. Based on the research that has been done on the student SMP Negeri 1 Teluk Kuantan who follow extracurricular sepak takraw to determine the extent to which the corelation between the eye and foot coordination with sepak takraw passing ability of students, obtained r = 0454 included the category enough. Tests of significance using the formula t test Significance. From the calculation results are known t = 2.97, while t table = 1.697. So t = 2.97> t table = 1.697. Then the conclusion can be drawn as follows: There is a significant corelation between the eye and foot coordination with passing ability in the game of sepak takraw at students of SMP Negeri 1 Teluk Kuantan "accepted.Keywords : Coordination, Eye-foot, Passing, Sepak Takraw